2000
DOI: 10.1021/bi992894+
|View full text |Cite
|
Sign up to set email alerts
|

13C and Deuterium Isotope Effects Suggest an Aldol Cleavage Mechanism for l-Ribulose-5-phosphate 4-Epimerase

Abstract: On the basis of (13)C and deuterium isotope effects, L-ribulose-5-phosphate 4-epimerase catalyzes the epimerization of L-ribulose 5-phosphate to D-xylulose 5-phosphate by an aldol cleavage to the enediolate of dihydroxyacetone and glycolaldehyde phosphate, followed by rotation of the aldehyde group and condensation to the epimer at C-4. With the wild-type enzyme, (13)C isotope effects were 1.85% at C-3 and 1.5% at C-4 at pH 7, with the values increasing to 2.53 and 2.05% at pH 5.5, respectively. H97N and Y229F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 32 publications
0
39
0
Order By: Relevance
“…8). 23) In addition, MtnB is a homotetramer, as are the FucA, RibE, and RhuA enzymes. 14,18,24) These similarities suggest that MtnB is a new member of the FucA/ RibE/RhuA family and that these enzymes are related to each other evolutionally.…”
Section: Discussionmentioning
confidence: 99%
“…8). 23) In addition, MtnB is a homotetramer, as are the FucA, RibE, and RhuA enzymes. 14,18,24) These similarities suggest that MtnB is a new member of the FucA/ RibE/RhuA family and that these enzymes are related to each other evolutionally.…”
Section: Discussionmentioning
confidence: 99%
“…Lac Lee showed the power of isotope effects to deduce mechanism in his studies of L-ribulose-5-P 4-epimerase (42). He devised a way to degrade the xylulose-5-P product carbon by carbon and showed that there were over 2% 13 C isotope effects at C-3 and C-4.…”
Section: Reflections: Use Of Isotope Effectsmentioning
confidence: 99%
“…[19] This enzyme interconverts l-ribulose-5-phosphate and d-xylulose-5-phosphate, but requires a divalent metal ion. DXR appears to catalyze a very similar reaction, albeit slowly, in the absence of a metal.…”
mentioning
confidence: 99%